Aboriginalising the parole process: 'Culturally appropriate' adaptations and the Canadian federal parole system - Turnbull, S (SAGE Publications, 2014)
The increasing ‘diversity’ of penal populations in most western countries over the past three decades raises questions as to the fairness and appropriateness of established penal programmes and practices. In some jurisdictions, penal policy-makers and administrators are being forced to deal with the implications of offender diversities, including race, ethnicity, gender, culture and religion, in policy and planning. In Canada, the pervasive over-representation of Aboriginal individuals in prisons has led to calls for change in how the corrections and parole systems deal with Aboriginal prisoners. This article examines the advent of one ‘culturally appropriate’ adaptation of the parole process, the Elder assisted hearing, introduced in 1992 by the Parole Board of Canada as a means of (1) addressing the problem of over-representation and (2) being responsive to Aboriginal difference. It shows that the ‘Aboriginalisation’ of parole hearing formats is by no means a straightforward process, and is illustrative of the broader challenges that racial, cultural and gender differences pose to contemporary penality.